2014
DOI: 10.1063/1.4871665
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of combinatorial coevaporated thin film Cu2ZnSnS4 (II): Beneficial cation arrangement in Cu-rich growth

Abstract: Cu2ZnSn(S,Se)4 (CZTSSe) is an earth-abundant semiconductor with potential for economical photovoltaic power generation at terawatt scales. In this work, we use Raman scattering to investigate phase coexistence in combinatorial CZTS thin films grown at 325 or 470 °C. The surface of the samples grown at 325 °C is rough except for a prominent specularly reflective band near and along the ZnS-Cu2SnS3 (CTS) tie line in the Cu-Zn-Sn-S quaternary phase diagram. All structurally incoherent secondary phases (SnS2, CuS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…The values are in a good agreement with the experimental data reported previously for CZTS phase. 16,36,37 Small amounts of exsolved Cu 2-x S phases (≈470 cm −1 ) typically formed as an impurity during the fabrication of CZTS may be present in the assynthesized powders (Figure 4A,C).…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…The values are in a good agreement with the experimental data reported previously for CZTS phase. 16,36,37 Small amounts of exsolved Cu 2-x S phases (≈470 cm −1 ) typically formed as an impurity during the fabrication of CZTS may be present in the assynthesized powders (Figure 4A,C).…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…• C. 15,16 It can be depicted as follows: In Fig. 1, there are weak (111) SnS and (311) SnS signatures in the CZTS films sulfurized at 500 and 550…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, it follows the reported reaction pathways of forming the CZTS phase from the binary sulfides and the potential ternary phases created at low temperatures, as described by the sequential reactions: 15,16 2CuS + SnS + ZnS → Cu 2 SnS 3 + ZnS → Cu 2 ZnSnS 4 [1] E. A. Lund et al 16 showed the CuS-ZnS-SnS pseudo-ternary phase diagram (at 325…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20,39,[43][44][45]. The Sn-S subsystem includes three possible phases: SnS, Sn 2 S 3 , SnS 2 ; all these phases can be present between room temperature and 600 °C [46][47][48].…”
Section: B Equilibrium Conditions For Kesterite and Formation Of Secmentioning
confidence: 99%